2000
DOI: 10.1006/qres.2000.2166
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Prehistoric Landfall Frequencies of Catastrophic Hurricanes in Northwestern Florida from Lake Sediment Records

Abstract: Sediment cores from Western Lake provide a 7000-yr record of coastal environmental changes and catastrophic hurricane landfalls along the Gulf Coast of the Florida Panhandle. Using Hurricane Opal as a modern analog, we infer that overwash sand layers occurring near the center of the lake were caused by catastrophic hurricanes of category 4 or 5 intensity. Few catastrophic hurricanes struck the Western Lake area during two quiescent periods 3400–5000 and 0–1000 14C yr B.P. The landfall probabilities increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
300
4
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(318 citation statements)
references
References 22 publications
13
300
4
1
Order By: Relevance
“…One-sigma (black) and two-sigma (gray) age ranges are shown for each date, and a linear fit (black line) to the median of the highest probability one-sigma age ranges reveals a roughly constant sedimentation rate of 1.35 mm yr-1 throughout the 601 cm (or ~ 4450-year) record. One-sigma and two-sigma age ranges for the anomalous date at 268-269 cm, which was not included in the (Scileppi and Donnelly 2007), Western Lake in Florida (�) (Liu and Fearn 2000), and Mattapoisett Marsh in Massachusetts (�) (Boldt et al 2010) are shown alongside the LT (�) and HT (+) versions of the MLT1 record. MLT 1 Figure 1 -MLT1 and MLT2 radiocarbon-based age models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One-sigma (black) and two-sigma (gray) age ranges are shown for each date, and a linear fit (black line) to the median of the highest probability one-sigma age ranges reveals a roughly constant sedimentation rate of 1.35 mm yr-1 throughout the 601 cm (or ~ 4450-year) record. One-sigma and two-sigma age ranges for the anomalous date at 268-269 cm, which was not included in the (Scileppi and Donnelly 2007), Western Lake in Florida (�) (Liu and Fearn 2000), and Mattapoisett Marsh in Massachusetts (�) (Boldt et al 2010) are shown alongside the LT (�) and HT (+) versions of the MLT1 record. MLT 1 Figure 1 -MLT1 and MLT2 radiocarbon-based age models.…”
Section: Discussionmentioning
confidence: 99%
“…When longer time periods are considered, changes in local hurricane frequency are more likely to reflect larger-scale changes in storm climate (Woodruff et al 2008a). Other sediment-based paleohurricane records from the Caribbean, Northeastern U.S., and the northern Gulf of Mexico have documented significant multi-centennial to millennialscale variability in hurricane frequency similar to the centennial to multi-centennial variability identified in the Mullet Pond reconstruction, though the timing and extent of the variability differs somewhat among the records (Liu and Fearn 1993, Liu and Fearn 2000, Scileppi and Donnelly 2007, Donnelly and Woodruff 2007. Fearn (1993, 2000) identified low-frequency variability in the number of visible sand layers deposited by hurricanes impacting Western Lake, Florida.…”
Section: Comparisons With Other Paleohurricane Recordsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the case of hurricane overwash deposits (Liu and Fearn, 2000;Donnelly and Woodruff, 2007;Woodruff et al, 2009) it is difficult to ascribe erosional processes to the gaps for the records are composed of sand layers sandwiched within fine-grained sedimentary units in back barrier lagoons. Chronological gaps within beach ridge plains that record long-term TC histories (Nott, 2003;Nott et al, 2009;Forsyth et al, 2010) are possible via two causes; erosion and removal of ridges or periods of slower or no ridge building possibly associated with a quiescence in intense TC activity.…”
Section: Introductionmentioning
confidence: 99%